Coping with risk in agriculture : applied decision analysis - Hardaker, J. B., (CABI, 2015)
As with earlier editions, the aim of this book is to support better agricultural decision making by explaining what can be done nowadays in risk analysis and risk management. As before, the intended readership includes senior undergraduate or graduate students of agricultural and rural resource management, agricultural research workers, people involved in advising farmers, such as extension workers, financial advisers and veterinarians, some farmers themselves, and policy makers. Methods of risk analysis and management are evolving rapidly. This third edition includes some recent advances in both theory and methods of analysis. New material includes sections on state-contingent versus stochastic production functions and an introduction to the use of copulas for modelling stochastic dependency. Improvements in available software continue to expand the scope to better represent and model real-world risky choices, and this edition has updated its advice concerning use of contemporary software. The book has 13 chapters.